The distribution of Dermacentor reticulatus in the Czech Republic re-assessed: citizen science approach to understanding the current distribution of the Babesia canis vector - Daněk, Ondřej; Hrazdilová, Kristýna; Kozderková, Dominika; Jirků, Daria; Modrý, David (Parasites & vectors, 2022)
BACKGROUND: The range of the ornate dog tick Dermacentor reticulatus is rapidly expanding in Europe. This tick species is the vector of canine babesiosis, caused by Babesia canis, and also plays a role in the transmission of Theileria equi and Babesia caballi in equids. METHODS: The geographic range of D. reticulatus in the Czech Republic was re-assessed, and an up-to-date distribution map is presented based on material and data obtained during a nationwide citizen science campaign. Received and flagged individuals of D. reticulatus were also analysed for the presence of B. canis DNA. RESULTS: In striking contrast to historical records, D. reticulatus was found in all regions of the Czech Republic, with most reports coming from the southeast and northwest of the country. Between February 2018 and June 2021, the project team received 558 photo reports of ticks and 250 packages containing ticks. Of the former, 71.1% were identified as Dermacentor sp. with the remainder identified as Ixodes sp., Haemaphysalis sp., Argas sp. or Hyalomma sp. The majority of specimens in the subset of ticks that were received (N = 610) were D. reticulatus (N = 568, 93.7%), followed by Ixodes ricinus and Hyalomma spp. A total of 783 adult D. reticulatus, either received (568) or collected by flagging (215), were tested for the presence of B. canis DNA using species-specific nested PCR targeting part of the 18S rRNA gene; B. canis DNA was demonstrated in 22 samples (2.81%). CONCLUSIONS: The continuous spread of D. reticulatus in the Czech Republic was documented in this study. In addition, DNA of B. canis was also detected in a number of ticks, suggesting the establishment of B. canis in the Czech Republic. These results suggest that veterinarians need to consider the possibility of canine babesiosis even in dogs without a history of travel.
Keywords: psi; Ixodes; Babesia; Dogs; Citizen Science; Ixodidae; Babesiosis; klíště; Rhipicephalus sanguineus; Citizen science; zvířata; občanská věda; Europe; Dermacentor reticulatus; nemoci psů; babezióza; Czech Republic; infestace klíšťaty; Geographic distribution; Dog Diseases; Babesia canis; Animals; Tick Infestations; Česká republika; Dermacentor